The Impact of Social Networks on EITC Claiming Behavior - Wilson, Riley (The Review of Economics and Statistics, 2022)
Abstract Using the Social Connectedness Index (Bailey, Cao, Kuchler, Stroebel et al., 2018) to capture county-to-county Facebook linkages, I explore how county-level earned income tax credit (EITC) claiming behavior changes when the county's out-of-state social network is exposed to a newly implemented state EITC. Having more out-of-state friends face a state EITC shifts the composition of EITC claims toward more self-employment claiming. EITC-claiming households' income distribution also shifts, moving away from the EITC region with smaller credits, toward income levels that generate the largest EITC. This mimics the direct impacts of state-level EITC policies, consistent with social networks increasing information or salience about EITC policy.